Hindustāni Paddhati - Scano, Remo (Occhialì, 2019)
Hindustāni Paddhati is one of the two macro‐genres of the musical expression of the Indian subcontinent, which is identified, at least geographically, with the northern regions of India. This short work is a description of its subgenres: Dhrupad, Khayāl, Ṭhumrī and Ṭappā.